ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN METODE ALTMAN Z-SCORE - Rika Fitria Nur Aini; Ahmad Idris; Rafikhein Novia Ayuanti (COMPETITIVE, 2022)
The purpose of this study is to analyze the prediction of bankruptcy using the Altman Z-Score method at PT. Kalbe Farma Tbk for the period 2011-2019. This study uses a quantitative descriptive method. The data used is secondary data taken from financial statements. From the results of the study, it was found that PT. Kalbe Farma Tbk is included in the category of a healthy company and avoided bankruptcy during the 2011-2019 period. The financial health achieved by PT. Kalbe Farma Tbk is supported by increased sales, high total assets, and stable working capital every year. The benefits of the research are expected for company managers to maintain financial conditions and investors can take decisions to maintain their investment in PT. Kalbe Farma Tbk. And this company can be a financial benchmark for other pharmaceutical companies.